Monitoring the effect of active packaging films with silver-kaolinite using different packaging systems on the quality of beef meat - Z. A., Nur Hanani; Reich, F.; Tolksdorf, T.; Siemen, H.; Bandick, N. (Elsevier, 2022)
Active packaging films based on gelatin with silver-kaolinite (Ag-Kln) were developed and their effects on the quality and microbial growth of beef meat stored in different packaging systems (cling film, vacuum and modified atmosphere packaging) at 4 °C for 13 days were evaluated. The analysis revealed that Ag-Kln packaging films had no adverse effects on the pH and colour of the beef samples irrespective of the packaging system used. Beef meat in packaging with active films lost more weight (P < 0.05) than without active films for meat in the vacuum and modified systems on day 13. In general, these gelatin films with Ag-Kln showed the potential as antibacterial films and could enhance the shelf life of food products, however, further studies are required to establish the release rate of silver from packaging films, as well as test the efficiency of these materials under different storage conditions. In conclusion, this study revealed that gelatin film with silver-kaolinite is a promising antibacterial agent and preservation material for food shelf life extension.